The Impact of the Coronavirus Disease - 19 Pandemic on the Clinical Characteristics and Treatment of Adult Patients with Acute Appendicitis - An, Sanghyun; Kim, Hae-Rim; Jang, Sungwoo; Kim, Kwangmin (Frontiers in Surgery, 2022)
Purpose This study aimed to investigate the characteristics, severity, and treatment of adult patients with acute appendicitis in Korea over a 2-year period during the coronavirus disease (COVID-19) pandemic compared to those before the pandemic. We also investigated whether there were any changes in clinical characteristics of acute appendicitis before and after vaccination against the coronavirus. Methods We retrospectively reviewed the medical records of patients who were diagnosed with acute appendicitis at our institution between March 1, 2019, and August 31, 2021. We divided the patients into three groups (pre-pandemic, before vaccination, and after vaccination) and analyzed the clinical outcomes. Results The time from symptom onset to hospital arrival and the time from symptom onset to operation increased during the COVID-19 pandemic period compared to the pre-pandemic period. The rate of complicated appendicitis during the pandemic was higher than that before the pandemic. In addition, the number of new daily cases showed a positive correlation with the time from symptom onset to hospital arrival (OR, 0.03; 95% CI, 0.02 to 0.04; P < 0.001) and complicated appendicitis (OR, 1.002; 95% CI, 1.001–1.002; P = 0.0017). The vaccination rate showed a negative correlation with the time from symptom onset to hospital arrival (OR, −2.26; 95% CI, −3.42 to −1.11; P < 0.001) and complicated appendicitis (OR, 0.915; 95% CI, 0.84 to 0.996; P = 0.0404). Conclusions Employing hospital-wide efforts, such as screening by rapid PCR testing, to avoid further time delays, and nationwide efforts, such as vaccination, to shorten the time from symptom onset to hospital arrival, are necessary to maintain the quality of treatment of acute appendicitis during an infectious disease pandemic.